Assessment of fitness in patients with cystic fibrosis and mild lung disease. Issue 5 (May 1997) - McLoughlin, P; McKeogh, D; Byrne, P; Finlay, G; Hayes, J; FitzGerald, M X
Abstract : BACKGROUND: Maximal exercise testing is used in patients with cystic fibrosis to assess functional status and prognosis. The lactate threshold is an index of aerobic fitness with significant advantages over maximal exercise tests. This study was undertaken to determine if the lactate threshold might be identified, non-invasively, in adult patients with cystic fibrosis and mild lung disease by measurement of ventilatory and gas exchange parameters. METHODS: Ten subjects with mild cystic fibrosis (forced vital capacity (FVC) > 70% predicted) and 10 healthy controls undertook an incremental exercise test on a bicycle ergometer. Ventilation and gas exchange parameters were measured continually and arterialised venous blood pH, carbon dioxide tension (PCO2), and lactate concentrations were measured at intervals throughout the tests. RESULTS: In subjects with cystic fibrosis there was no significant difference between the mean gas exchange and lactate thresholds (mean difference 1.0 (95% confidence interval (CI) of the mean -1.5 to 3.44) ml/kg/min). In contrast, there was a significant difference between the mean ventilatory and lactate thresholds (3.8 (95% CI 0.9 to 6.7) ml/kg/min). Arterialised venous PCO2 increased significantly during the exercise tests. In healthy subjects the mean differences between these thresholds were not significantly different from zero and PCO2 fell significantly during the tests. CONCLUSIONS: The ventilatory threshold significantly overestimates the lactate threshold in subjects with cystic fibrosis induced lung disease because of impaired carbon dioxide excretion during exercise. However, the gas exchange threshold may be used to determine the lactate threshold in this patient group.